2016
DOI: 10.1039/c6tc02945k
|View full text |Cite
|
Sign up to set email alerts
|

Quinoxaline-based cross-conjugated luminophores: charge transfer, piezofluorochromic, and sensing properties

Abstract: Quinoxaline-based cross-conjugated luminophores have been constructed and their charge transfer, piezofluorochromic, and sensing properties have been systematically investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 68 publications
2
19
0
Order By: Relevance
“… 32 In addition, the quinoxaline core has the advantage of low synthetic cost, and its pyrazine heterocycle provide a facile chemical modification possibility. 33 , 34 The substituents on the quinoxaline core are found to be critical to the photovoltaic performance, and the thienyl substituent based TQ2 shows much superiority to its phenyl analogue TQ1 in terms of hole extraction and conduction, which was rationalized by a series of comparative studies including photoluminescence (PL) quenching, hole mobility/conductivity measurement and single crystal analysis. The best performing PSCs employing TQ2 as the hole transporting layer exhibit a maximum PCE of 19.62% (area of 0.09 cm 2 ), outperforming that of spiro-OMeTAD (18.54%) under the same conditions.…”
Section: Introductionmentioning
confidence: 99%
“… 32 In addition, the quinoxaline core has the advantage of low synthetic cost, and its pyrazine heterocycle provide a facile chemical modification possibility. 33 , 34 The substituents on the quinoxaline core are found to be critical to the photovoltaic performance, and the thienyl substituent based TQ2 shows much superiority to its phenyl analogue TQ1 in terms of hole extraction and conduction, which was rationalized by a series of comparative studies including photoluminescence (PL) quenching, hole mobility/conductivity measurement and single crystal analysis. The best performing PSCs employing TQ2 as the hole transporting layer exhibit a maximum PCE of 19.62% (area of 0.09 cm 2 ), outperforming that of spiro-OMeTAD (18.54%) under the same conditions.…”
Section: Introductionmentioning
confidence: 99%
“…TVA emits blue-green light at 498 nm in nonpolar cyclohexane, whereas its solutioni nD MF emits orange light with am aximum emission at 551 nm, exhibiting as ignificantly bathochromic shifto f5 3nmw itht he increased solvent polarity.M eanwhile, the F F decreases from 82 %i nn onpolar cyclohexane to 9% in polar DMF,s uggestingatypical ICT character. [17] The theoretical simulation results also support the existence of an ICT effect for these luminophores. DFT calculations for TVA, CPVA,a nd DTVA were performed using Gaussian09a t the B3LYP.6-31G (d, p) level.…”
mentioning
confidence: 54%
“…In contrast, remarkable solvent‐dependent emission of TVA can be observed as depicted in Figure b. TVA emits blue‐green light at 498 nm in nonpolar cyclohexane, whereas its solution in DMF emits orange light with a maximum emission at 551 nm, exhibiting a significantly bathochromic shift of 53 nm with the increased solvent polarity. Meanwhile, the Φ F decreases from 82 % in nonpolar cyclohexane to 9 % in polar DMF, suggesting a typical ICT character …”
Section: Figurementioning
confidence: 99%
“…Also, the bathochromic shift only in the PL profile of both the compounds suggested that, first the absorption occurs on the vibrational level in the excited state, which then stabilized to the low-energy state owing to the charge-transfer character, and then finally decayed radiatively to the ground state. 22…”
Section: Resultsmentioning
confidence: 99%